Open issues in router buffer sizing. - Dhamdhere, Amogh
Recent research results suggest that the buffers of router interfaces can be made very small, much less than the link's and width-delay product, without causing a utilization loss, as long as the link carries many TCP flows. In this letter we raise some concerns about the previous recommendation. We show that the use of such small buffers can lead to excessively high loss rates (up to 5%-15%in our simulations) in congested access links that carry many flows. Even if the link is fully utilized, small buffers lead to lower throughput for most large TCP flows, and significant variability in the per-flow throughput and transfer latency. We also discuss some important issues in router buffer sizing that are often ignored
Keywords: Computer systems organization; Computer communication networks; Internetworking; Routers; Performance of systems; Software; Operating systems; Communications management; Buffering; Design; Measurement; Performance; Theory